O mal estar de uma identidade regional : representações do trabalhador negro escravizadoe seus descendentes na historiografia Rio-grandense - Assis Brasil, Alcides Lima, Salis Goulart e Dante de Laytano - Lima, Maurício Lopes (2014)
This term paper examines the process of building an ethno-historical identity for the Rio Grande do Sul through its historiography. We evaluate the ways representations about the enslaved black worker and his descendants role in this society formation process. The cuttings were done by author/work of a way that represented different stances, in different periods, but that, in the set, the majority historiography Sul-Rio-Grandense position about the topic. We started from the 1880s with the ―História Popular do Rio Grande do Sul works from Alcides de Mendonça Lima and ―História da República Rio-grandense from Joaquim Francisco de Assis Brasil, passed for 1920 s when the book ―Formação do Rio Grande do Sul was analyzed from Jorge Salis Goulart, getting into the texts about the black person topic from Dante de Laytano, in 1940s to 1950s. We searched the ―habitus‖ concept from Pierre Bourdieu to understand the representations built by historian agent as manifestations that are according to the historical process, but that, at the same time, were constantly prepared again from the representations, many times arbitrary and distorted, built by this historiography. It is on ―habitus‖ that we found a neutralization process of these representations. We looked for, besides, to lead the representations analysis while world social views held in a perspective class since these historians speeches have social address and are justified with conservative maintenance and improvement postures of the power´s relation in that historically, enslaved black workers and their descendants were oppressed. At the same time, we proposed the politician s field appreciation necessity of intellectual work. We chose to hold the debate from historiographic works, considering legitimate to emphasize the domineering and prescriptive part of these speeches that a lot of times are presented as if they were the correct unique and natural view of the Sul-Rio-Grandense ethnic identity essence